The Examination of Government Regulation Number 28 of 2022 From a Pancasila Point of View - Evy Harjono; Wartoyo, Franciscus Xaverius; Mulyani, Rita; Maghribi, Genta; Batubara, Aznina Lembayung; Harlingan, David (Inovasi Pratama Internasional. Ltd, 2024)
Indonesia as a democratic country that emphasizes the rule of law as the main foundation, makes Pancasila as the moral and philosophical foundation for the constitution and laws and regulations. This research aims to evaluate the consistency of Government Regulation Number 28 Year 2022 on the Management of State Receivables with the principles of Pancasila, as well as to assess the extent to which its practical implementation reflects the moral and philosophical values of Pancasila. The method used in this research is juridical-normative with a conceptual and statutory approach, accompanied by qualitative descriptive analysis of relevant statutory documents and legal doctrine. The results of the analysis highlight the importance that Government Regulation No. 28 Year 2022 must comply with the existing legal hierarchy, as well as consistently reflect the principles of Pancasila as a moral and philosophical foundation in the regulation of state receivables. Nonetheless, the addition of new rules concerning liability for state receivables raises debates about consistency and social justice. Therefore, it is important for the government to ensure that the implementation of the rules not only considers the legal and financial aspects, but also the social and humanitarian impacts on the individuals involved. Success in regulating state receivables should be measured by the extent to which the principles of Pancasila are respected and social justice is realized in the process, which will help strengthen the foundations of democracy and the rule of law in Indonesia.